Acción Antimicrobiana de los Aceites Naturales Sobre el Streptococcus Mutans: Una revisión Sistemática (2020)
Streptococcus mutans is a Gram-positive, facultative anaerobic bacteria normally found in the human oral cavity, forming part of dental plaque or dental biofilm. It is associated with the onset and development of dental caries and is the bacterium with the highest incidence in the development of the same. Objective: To determine the antimicrobial action that natural oils have on streptococcus mutans from a systematic review. Materials and Methods: It corresponds to a descriptive observational study, for which a systematic review will be carried out in which we seek to provide a detailed analysis of the inhibitory effects that natural oils have on streptococcus mutans. Results: From the articles analyzed, it could be concluded that there are more than 30 varieties of oils with an antimicrobial effect on streptococcus mutans; ginger presents the highest differentiating value as regards its effectiveness on dead cells (98%) and the concentrations used vary from 0.1 mg/Dl to 6 mg/Dl. Conclusions: A total of 39 natural oils were analyzed, 95% of which present antimicrobial properties and 5% are in studies (oils concentrated in citrus fruits) to establish if they have antimicrobial capacity; according to this, the oil with the highest antimicrobial rate is ginger oil with a 99% inhibition rate purchased with the lowest rate, which was 74% corresponding to Cymbopogon citratus oil with 74%.